(untitled) (PRÁXIS EM SAÚDE, 2025)
This article investigates the use of expressive resources in Harm Reduction at festivals, where the consumption of psychoactive substances (PAS) occurs amid sensory stimuli and emotional and symbolic experiences. The methodology consisted of an artistic workshop with meditative practice and symbolic expression of narratives about experiences with PAS. The objective was to evaluate the potential of artistic practices in integrating these experiences. The results show that the workshop facilitated the elaboration of content related to past experiences as well as emerging images and sensations. It is concluded that artistic spaces and collective listening help reconstruct personal narratives, enhancing awareness and promoting care in Harm Reduction both inside and outside festivals.